An Analysis Of Character Education Values In English Textbook “When English Rings The Bell” For Eight Grade Students Used By Mts Nurul Yaqin - Memy Wardani Elthia; Nur Alfilail (PT PUSTAKA CENDEKIA GROUP, 2026)
Character education has become a fundamental aspect of the Indonesian education system, aiming to develop students’ moral values alongside their academic achievement. One of the ways character education is implemented is through textbooks used in classroom learning. This study aimed to analyze the character education values reflected in the English textbook When English Rings the Bell for eighth-grade students. The research employed a qualitative content analysis design. The data were obtained from dialogues, reading texts, exercises, illustrations, and learning activities contained in the textbook. Data were collected through document analysis.The analysis was based on the five core character education values promoted by the Indonesian Ministry of Education, namely religiosity, nationalism, independence, cooperation, and integrity. The findings revealed that all five character education values were represented in the textbook. Independence emerged as the most dominant value, followed by cooperation, integrity, nationalism, and religiosity. These values were reflected through individual assignments, group discussions, role-play activities, cultural topics, and expressions of gratitude and responsibility. The findings indicate that When English Rings the Bell not only supports students’ English language development but also contributes to character building. However, the unequal distribution of character values suggests that teachers should provide supplementary activities to reinforce less-represented values. Therefore, the textbook can be considered an effective medium for integrating character education into English language learning while supporting the objectives of the Indonesian curriculum.